2017
DOI: 10.1002/lno.10533
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic conditions drive significant variability in nutrient processing by a common Caribbean sponge, Ircinia felix

Abstract: Coral reefs typically occur in oligotrophic waters, where tight recycling of energy and nutrients is essential in order to support their high productivity. Sponges are efficient filter feeders that host diverse and abundant microbial communities that often contain members capable of carrying out complex nutrient transformations. Consequently, sponges often act as significant sources of bioavailable forms of nitrogen and phosphorus while acting as sinks for dissolved organic carbon (DOC). However, little attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 58 publications
(88 reference statements)
5
49
2
Order By: Relevance
“…It is thought that sponges primarily consume labile, rather than refractory, forms of DOC (Yahel et al 2003, de Goeij et al 2008b, and higher rates of uptake and detritus production have been found for sponges incubated with algal-versus coral-derived DOC (Rix et al 2017). Evidence suggests that there may be a direct relationship between ambient DOC concentrations and DOC uptake, and there may be a threshold for DOC uptake (Mueller et al 2014, McMurray et al 2016, Archer et al 2017, Morganti et al 2017. Our results only support such a relationship for the HMA species Agelas tubulata, Verongula reiswigi, V. gigantea, and the LMA species Callyspongia plicifera, although additional data are needed to further examine this putative relationship for the species investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is thought that sponges primarily consume labile, rather than refractory, forms of DOC (Yahel et al 2003, de Goeij et al 2008b, and higher rates of uptake and detritus production have been found for sponges incubated with algal-versus coral-derived DOC (Rix et al 2017). Evidence suggests that there may be a direct relationship between ambient DOC concentrations and DOC uptake, and there may be a threshold for DOC uptake (Mueller et al 2014, McMurray et al 2016, Archer et al 2017, Morganti et al 2017. Our results only support such a relationship for the HMA species Agelas tubulata, Verongula reiswigi, V. gigantea, and the LMA species Callyspongia plicifera, although additional data are needed to further examine this putative relationship for the species investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, an increasing number of sponge species have been found to feed on DOC (Yahel et al 2003, de Goeij et al 2008b, Ribes et al 2012, Mueller et al 2014, McMurray et al 2016, Archer et al 2017, Hoer et al 2018, Morganti et al 2017, and a link between DOC uptake and detritus production has been established for additional cryptic sponge species (Alexander et al 2014, Rix et al 2016. While it was generally thought that sponge species with dense assemblages of symbiotic microbes -i.e.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors likely acted in concert, leading an underestimation of the ingested or produced DOM (as in Jiménez and Ribes ). Of note in this context is that sponges, including one of the species analyzed herein, I. felix , can be both sources and sinks of organic matter (e.g., Archer et al ). This continual production and consumption in the chambered water mass would obscure overall trends in behavior and could similarly stymie attempts to determine uptake or production over time.…”
Section: Discussionmentioning
confidence: 99%